The Use of Mebendazole in COVID-19 Patients: An Observational Retrospective Single Center Study - Mostafa W. Galal; Mahmoud Ahmed; Yanqiu Shao; Chao Xing; Wael Ali; Abd Elhamid Baly; Abdallah Elfiky; Khaled Amer; John Schoggins; Hesham A. Sadek; Zeinab N. Gobara (Advances in Virology)
Background. An in-silico screen identified mebendazole with potential antiviral activity that could be a repurposed drug against SARS-CoV-2. Mebendazole is a well-tolerated and cheap antihelminthic agent that is readily available worldwide and thus could be a therapeutic tool in the fight against COVID-19. Methods. This is an observational retrospective study of PCR-confirmed COVID-19 patients who received mebendazole with the intention-to-treat. The study included an inpatient cohort (157 inpatients) and an outpatient cohort (185 outpatients). Of the 157 inpatients and 185 outpatients, 68 (43.3%) and 94 (50.8%) received mebendazole, respectively. Patients who presented within the same timeframe but did not receive mebendazole were used as controls. Patients received standard-of-care treatment including remdesivir, dexamethasone, and anticoagulants as deemed necessary by the treating physician. The following clinical outcomes were evaluated: for the inpatient cohort, length of stay (LOS) at the hospital, need for ventilation (combined invasive and noninvasive), and mortality; for the outpatient cohort, time to symptom resolution, need for hospitalization, and mortality. Results. For the inpatient cohort, the median age did not differ between the treatment and control groups; 62 (56, 67) vs. 62 (56, 68), P, and there was a comparable proportion of males in both groups; 43 (63%) vs. 55 (62%), P=0.85. The hospital LOS was 3.5 days shorter in the treatment group compared to the control group (P<0.001). There were fewer patients who required invasive or noninvasive ventilation in the treatment group, 2 (2.9%) vs. 7 (7.9%), and the mortality rate is lower in the treatment group, 3 (4.4%) vs. 8 (9.0%), though the differences did not reach statistical significance. For the outpatient cohort, the median age was lower in the treatment group compared with the control group; 40 (34, 48) vs. 48 (41, 54), P<0.001. There was a comparable proportion of males between both groups; 50 (53%) vs. 52 (57%), P=0.59. Patients in the treatment group were 3.3 days closer to symptom resolution (P<0.001). There were numerically fewer patients requiring hospitalization in the treatment group compared with the control group, 3 (3.2%) vs. 6 (6.6%), though this did not reach statistical significance (P=0.33). Conclusion. In this retrospective observational study, the use of mebendazole in COVID-19 patients was associated with shorter hospitalizations in the inpatient cohort and shorter durations of symptom resolution in the outpatient cohort. The findings from this small observational study are hypothesis-generating and preclude drawing conclusions about clinical efficacy. Further studies are needed to examine the role of mebendazole in the treatment of COVID-19 patients.